2015
DOI: 10.1039/c4ce01428f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal nucleation of salicylic acid in organic solvents

Abstract: Nucleation of salicylic acid in different solvents becomes gradually more difficult in the order: chloroform, ethyl acetate, acetonitrile, acetone, methanol and acetic acid. By comparing the results of metastable zone width and induction time experiments new insights are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 47 publications
6
80
0
Order By: Relevance
“…Parameters C and D are determined by the properties of the crystal growth system similar to the parameters A and B respectively of the BCF model. In the present work, C is treated as temperature-dependent, while D is considered temperature-independent, again using equation (5). The solid-liquid interfacial energy in equation (8) appears in formulae describing the radius of the two-dimensional critical nuclei that forms on the surface and is the source of new growth steps.…”
Section: Theorymentioning
confidence: 99%
“…Parameters C and D are determined by the properties of the crystal growth system similar to the parameters A and B respectively of the BCF model. In the present work, C is treated as temperature-dependent, while D is considered temperature-independent, again using equation (5). The solid-liquid interfacial energy in equation (8) appears in formulae describing the radius of the two-dimensional critical nuclei that forms on the surface and is the source of new growth steps.…”
Section: Theorymentioning
confidence: 99%
“…An experimental apparatus identical to that described by Mealey et al 17 was employed to simultaneously monitor 20 individual nucleation experiments. Solutions were transferred from bath A at 55 C to bath B held at a temperature where the solutions were supersaturated (T supersat ).…”
Section: Induction Time Measurementmentioning
confidence: 99%
“…17,24 Here we have used the lognormal cumulative distribution function (LCDF) and the exponential-based function of Jiang and ter Horst. 17,24 Here we have used the lognormal cumulative distribution function (LCDF) and the exponential-based function of Jiang and ter Horst.…”
Section: Rate Of Nucleation In Different Solventsmentioning
confidence: 99%
“…[15] Different solvents can cause solute molecules to assumev astly different conformations, with the result that dif-ferent solvents can nucleate different conformational polymorphs. [16] After statistically measuring the induction time in several organic solvents, [17] our group has recently shown that the rate of nucleationo fs alicylica cid, as mall inflexible organic molecule, is relatedt ot he strength with which the solvent binds the molecule in solution. [6] As trong positive correlation is shown between the interfacial energy calculated from induction times and several experimental and modelled variables describing solvent-solute bonding at SA'sc arboxyl group:t he carbonyl peak shift in the Raman spectrumf or the salicylic acid monomer,t he DFT-derived (1:1) binding energyt ot he carbonyl group, the calorimetrically-derived enthalpyo fs olvent-solutei nteraction, and the DFT-derived solvation energy.…”
Section: Introductionmentioning
confidence: 99%